STUDI RELEVANSI KURIKULUM KOMPETENSI KEAHLIAN TEKNIK KENDARAAN RINGAN DI SMKN 5 SURAKARTA DENGAN KEBUTUHAN DUNIA INDUSTRI SAAT SISWA MELAKSANAKAN PRAKERIN - Farhandika Akbar; Budi Harjanto; Ngatou Rohman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2020)
The purpose of this study was to find out: (1) Competency of expertise discussed in Light Vehicle Engineering Expertise Competence of SMKN 5 Surakarta; (2) Competency of expertise obtained by students of Light Vehicle Engineering Skills Competency of SMKN 5 Surakarta prior to the implementation of internship; (3) Competency of expertise needed by the industrial world from students when implementing internship; (4) Relevance of the Curriculum for Light Vehicle Engineering Competence of SMKN 5 Surakarta with the needs of the relevant industrial world from the implementation of internship. This type of research is a qualitative descriptive study. Sources of information in research are productive teachers and workshop or industry heads with information obtained by interviews and analysis of archives. The research process was carried out in two glasses, namely: first, observing the Competency of Light Vehicle Engineering Skills (KKTKR) of SMK 5 Surakarta to study the curriculum needed, comparing the competencies needed before students use apprenticeship. This competency is then recorded and arranged in the form of a simple questionnaire. The second stage is to bring a list of competencies taken before student internship to the industry to see its relevance to the needs of the industrial world. The results of this study indicate that the competencies discussed in the learning skills at KKTKR SMK 5 Surakarta provide the latest 13 revised curriculum in 2017. Competencies obtained from students in apprenticeship are competencies obtained from semester 1 to 3 mathematics lessons. These competencies are provided with competencies from compulsory subjects in class X, namely Image of Automotive Engineering, Basic Automotive Technology, and Automotive Basic Work. Equipped with competencies from the subjects of Light Vehicle Engine Maintenance, Chassis Maintenance and Transfer of Light Vehicle Power, and Light Vehicle Electrical Maintenance approved in semester XI 3. Competencies needed by the industry to be communicated to student apprenticeships related to automotive basics, such as tools -Technical tools such as hand tools and measuring instruments, general vehicle knowledge, security in workshop work. The industry also emphasizes the work relations of students who are good as supporters of implementing internship. The results of the study can be seen from two sides. Formally, the relevance level is more than 90%. While the implementation, there are findings where the level of understanding of students is still lacking including the basic automotive competencies that should have mastered